The Anatomic Pathology laboratory adjustments in the era of COVID-19 pandemic: The experience of a laboratory in a Portuguese central hospital - Lamas, Nuno Jorge (2020)
The coronavirus disease 2019 (COVID-19) pandemic has dramatically changed the world over the past weeks, with already 8,25 million infections and 445,000 deaths worldwide, leading to an unprecedented international global effort to contain the virus and prevent its spread. The emergence of novel respiratory viruses such as the SARS-CoV-2 creates dramatic challenges to the healthcare services, including surgical pathology laboratories, despite their extensive daily experience in dealing with biological and chemical hazards. Here, we cover important aspects on the knowledge on COVID-19 gathered during the first six months of the pandemic and address relevant issues on human biological sample handling in the Anatomic Pathology laboratory in the context of COVID-19 global threat. In addition, we detail our strategy to minimize the risk of contamination upon exposure to the different biological products received in the laboratory, which can be of general interest to other laboratories worldwide. Our approach has enabled a safe work environment for laboratory staff, while ensuring the maintenance of high quality standards of the work performed. In times of uncertainty and given the lack of specific guidelines directed at Anatomic Pathology services to better deal with the global COVID-19 public-health emergency, it is essential to share with the community rigorous methodologies that will enable us to better cope with probable novel waves of COVID-19 infection and other viruses that will possibly arise in the near future.